Bioremediation of Crude Oil Using Bacterium from the Coastal Sediments of Kish Island, Iran - Maryam SADEGHI HADDAD ZAVAREH; Gholamhossein EBRAHIMIPOUR; Mohsen SHAHRIARI MOGHADAM; Javad FAKHARI; Tahereh ABDOLI (Iranian Journal of Public Health, 2016)
Background: Much of the environment is affected by petroleum contamination. It imposes serious health problems for humans as well as serious environmental impact. Bioremediation is an important consideration for removing environmental pollutants because, compared with other technologies, it incurrs lower costs and is environmentally compatible.